DESAIN LABEL KEMASAN SIJI USED COOKING OIL AROMA THERAPY CANDLE - Chrissandy, Ruby; Putri, Grivenna Lavender (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
The Covid-19 pandemic has had an impact on micro, small adn medium enterprises (MSME), conventional transaction and public consumption have decreased. Pigijo is a Non-Governmental Organization (NGO) that support MSME in marketing their products. Pigijo also supports the Merdeka Belajar Kampus Merdeka program by providing opportunities for students to do internships. One of their partners, Rumah Inspirasi Jogja (Rumijo), wants to increase businesses on local communities. Rumijo is a non-governmental organization that teaches about sustainable tourism, waste management and advancing the local community's economy. Rumijo's program is making aromatherapy candle products made from used cooking oil. The result is products that are marketable, environmentally friendly and promote the community's economy. The problem is that this product requires an attractive packaging label design for consumers. The purpose of this activity is to produce a packaging label design for this product. Methods of implementing activities through the stages of problem identification, problem formulation, research, production and presentation. Good packaging design can influence consumer perceptions of product quality. The packaging label design for this aromatherapy candle product made from used cooking oil was made with the visual elements used to be able to speak as an environmentally friendly, attractive product, and a local Yogyakarta product. Rumijo was very impressed with the design and hopes to help increase the value of the candle product. The results of the design carry the concept of natural, elegant, growing and beautiful, with a design strategy that carries Yogyakarta's unique flora as a visual identity and is named Siji. Pandemi Covid-19 berdampak pada pengusaha UMKM, pola transaksi dan konsumsi masyarakat menurun. Pigijo merupakan Lembaga Swadaya Masyarakat (LSM) yang membantu UMKM produk wisata dalam memasarkan produknya. Pigijo juga mendukung program Merdeka Belajar Kampus Merdeka dengan memberi kesempatan pada mahasiswa magang. Salah satu mitranya yaitu Rumah Inspirasi Jogja (Rumijo) membutuhkan peningkatan bisnis lokal agar berdampak langsung pada masyarakat lokal. Rumijo adalah lembaga swadaya masyarakat yang mengajarkan tentang wisata berkelanjutan, pengelolaan sampah dan memajukan ekonomi masyarakat sekitar. Program yang dibuat Rumijo membuat produk lilin aroma terapi berbahan minyak jelantah. Hasilnya menjadi produk yang berdaya jual, ramah lingkungan dan memajukan ekonomi masyarakat. Permasalahannya produk ini memerlukan desain label kemasan yang menarik untuk konsumen. Tujuan kegiatan ini adalah menghasilkan desain label kemasan untuk produk ini. Metode pelaksanaan kegiatan melalui tahapan identifikasi masalah, merumuskan masalah, riset, produksi dan presentasi. Desain kemasan yang baik dapat mempengaruhi persepsi konsumen pada kualitas produk. Desain label kemasan dari produk lilin aroma terapi berbahan minyak jelantah ini dibuat dengan unsur visual yang digunakan harus mampu berbicara sebagai produk yang ramah lingkungan, menarik, dan produk lokal Yogyakarta. Rumijo sangat berkesan dengan desain tersebut dan berharap dapat membantu meningkatkan nilai produk lilin tersebut. Hasil desain mengusung konsep alami, anggun, tumbuh dan indah, dengan strategi perancangan mengusung flora khas Yogyakarta sebagai identitas visual dan diberi nama Siji.